Evaluating the Critical Success Factors of Industrialised Building System Implementation in Nigeria: The Stakeholders’ Perception (International Journal of Built Environment and Sustainability, 2018)
Globally, the adoption of Industrialised building system (IBS) has been acknowledged as a panacea for housing delivery performance. However, in most developing nations, especially Nigeria, its successful adoption is confronted with myriad of factors that are differently perceived by stakeholders resulting in poor performance and low uptake. The focus of this study is, therefore, to identify and evaluate those inhibiting factors as perceived by key construction stakeholders in the Nigerian construction industry. Initially, sixty-four (64) factors were identified through literature and structured interview. After which, a panel of experts, through Delphi method, considered forty-seven (47) of the factors contextual to IBS performance in Nigeria. 210 (70%) multidisciplinary construction professionals responded to the 300 administered questionnaires anchored on a Likert scale of I-5, (1-least significant to 5-Most Significant). Mean score approach was employed for data analysis. All the success factors were perceived to be critical. However, while forty (40) factors were perceived to excise high influence, seven (7) factors were found to moderately influence IBS performance. The five (5) critical success factors (CSFs) based on mean score (MS) are; Clear and precise goals (3.986), knowledge & skills (3.976), planning & control (3.948), top management support (3.938), and transportation (3.924). Having the knowledge of factors critical to IBS performance will assist key stakeholders' in their decision-making towards achieving effective project delivery.
Keywords: Industrialised Building System; Critical Success Factors; Project Performance; Mass Housing Projects; Nigerian Construction Industry